In vitro membrane damage induced by half-fin anchovy hydrolysates/glucose Maillard reaction products and the effects on oxidative status in vivo. Issue 2 (4th January 2018) - Song, Ru; Shi, Qingqing; Yang, Peiyu; Wei, Rongbian
Abstract : Through induced H2 O2 generation in vitro, HAHp(9.0)-G MRPs increased the antioxidant status in normal mice after short-term intake. Abstract : Membrane damage via the Maillard reaction products of half-fin anchovy hydrolysates and glucose (designated as HAHp(9.0)-G MRPs) was evaluated using an in vitro Escherichia coli ( E. coli ) model. The incubation of HAHp(9.0)-G MRPs led to a significant increase in outer and inner membrane permeability. Furthermore, membrane integrity was seriously destroyed, as observed by scanning electron microscopy and indicated by the decreased fluorescence signal of 4′, 6-diamidino-2-phenylindole stain. Interestingly, HAHp(9.0)-G MRPs induced significant hydrogen peroxide (H2 O2 ) production in E. coli after 3 h of incubation, which contributed to the antibacterial activity of HAHp(9.0)-G MRPs. As one of the reactive oxygen species, excess H2 O2 in vivo might impair the antioxidant balance. Therefore, the oxidative status of healthy mice after short-term intake of HAHp(9.0)-G MRPs was investigated. After the administration of HAHp(9.0)-G MRPs at low dose (0.1 g per kg per day body weight) and high dose (1.0 g per kg per day body weight) for 14 days, the body weight of female mice decreased, and the body weight of male mice increased. However, the administration of HAHp(9.0)-G MRPs did not affect the hepatic antioxidant defense in either female or male mice. Some positive responses, like increased superoxide dismutase (SOD) and glutathione peroxidase (GPx) as well as decreased lipid peroxidation (LPO) content, were detected, especially in liver. Though the decrease in catalase activity indicated that the glycation compounds from HAHp(9.0)-G MRPs might be absorbed in vivo, the lower SOD/GPx ratios of HAHp(9.0)-G MRPs-fed groups than those of the normal groups also suggested that the administration of HAHp(9.0)-G MRPs could reduce LPO stress in mice. Our results suggest that a higher antioxidant status could be generated in the healthy animals after fed with HAHp(9.0)-G MRPs for 14 days.